Inovasi Pembelajaran Pendidikan Agama Islam Di Masa Pandemi Covid-19 - Ahmad; Hasnawati; Hasirah (Jurnal Edukasi, 2022)
The concept of online learning is a form of innovation; of course, it cannot be separated from the role of technology. Technology can simplify all needs in the teaching and learning process. In line with Tounder's opinion, digital technology in educational institutions is a means of supporting learning, either as a means of accessing learning resource information or as a means of supporting learning activities and related tasks. As technology continues to develop, there are currently many platforms that can help implement online learning. Learning innovation in the form of educational technology can be defined as theory and practice in designing, developing, utilizing, managing, and assessing processes and resources for learning. The internet is a relevant media if used to support the quality of Islamic religious education. Because it can provide convenience and speed in conveying information, the PAI learning process can run effectively and efficiently.